O processo de construção do conhecimento geográfico na formação inicial de professores - SOUZA, Vanilton Camilo de (2009)
This work deals with a research about the knowledge construction process made by UFG, UCG and UEG students of geography licentiateships. The aims of this research are: 1) to characterize the knowledge construction practices in the beginning formation of the students of geography licentiateships from these Goianas universities; 2) to identify the formation practices that give power to these professionals academic formation and the practices that make it fragile. 3) to describe and analyze the geography teacher s beginning formation phases, identifying the most meaningful in the knowledge construction; 4) To identify the present inter-faces between the geographical contents and concepts of the curricular subjects with the know how constructed by the students of geography licentiateship during their beginning formation, and finally, 5) to construct the way that the student, in their beginning formation set up with the geographical and educational knowledge. This research has qualitative nature of ethnographic basis, and supports itself in the dialectic as basic principles to the analysis and interpretation of the results. The datum collection was done under the formation accompaniment of four groups since the half of the course. In the formation accompaniment of these students, we had two appointments for semester with each group. In these appointments, we used the collective interview, the narrative production and the individual interviews as main instruments of datum collection. Another mechanism was the analysis of documents. For that, pedagogical projects of Geography teacher formation, the teaching plans of Urban Geography, Geography Didactic and the Supervised Traineeship were analyzed to broaden the comprehension of the knowledge construction process during the formation of these teachers. As theoretical reference, the datum were analyzed, on the one hand, by the researcher teacher notions, reflexive teacher, and the articulation between theory and practice as participant extents of the constructed knowledge, and, on the other hand, by Bachelard and Vigotski contributions as orientations for the comprehension of the knowledge construction process of the Geography students in their beginning formation. The datum revealed how it is complex the formation process of geography teacher. Such complexity is essentially due to the fact that Geography students need mediation processes to perform their thought, and thus, construct their knowledge. The research revealed, yet, a huge amount of obstacles that make such process difficult